SPECTROPHOTOMETRIC METHODS FOR THE DETERMINATION OF TRAZODONE HYDROCHLORIDE IN PRESENCE OF ITS ALKALINE DEGRADATION PRODUCT - Abdelraoof, Ahmed (Innoriginal: International Journal of Sciences, 2017)
Introduction: Simple, sensitive, precise and low-cost spectrophotometric methods were developed for the determination of trazodone hydrochloride in the presence of its alkaline degradation product in bulk powder and in a pharmaceutical preparation. The proposed spectrophotometric methods involve, second derivative (2D), ratio derivative (1DD), ratio difference, Mean centering, bivariate and dual wavelength. Results and discussion: The regression plot was found to be linear over the range of 1-30 Âµg mL-1 Conclusions. These methods were validated and successfully applied for the determination of trazodone hydrochloride Trittico Â® tablets. The obtained results were statistically compared with those of the reported method by applying t-test and F-value at 95% confidence level, and no significant difference was observed regarding accuracy and precision. Keywords: Trazodone hydrochloride, Second derivative, Ratio derivative, Ratio difference, Mean centering, Bivariate, Dual wavelength.